Risk factors for osteoporosis in liver cirrhosis patients measured by transient elastography. Issue 20 (May 2018) - Zheng, Jian-ping; Miao, Hai-xiong; Zheng, Shao-wei; Liu, Wei-le; Chen, Chu-qun; Zhong, Hao-bo; Li, Sheng-fa; Fang, Yong-ping; Sun, Chun-han
Abstract : Abstract: Osteoporosis or osteopenia is a common complication in patients with cirrhosis, but little is known about the risk factors for the occurrence of osteoporosis. Patients with liver cirrhosis due to chronic virus infection and alcoholic abuse were enrolled. Bone mineral density (BMD) was determined using dual-energy x-ray absorptiometry (DXA). Osteoporosis was diagnosed according to WHO criteria. The severity of liver stiffness was measured by Fibroscan. Demographic data, such as age, gender, weight, height, and body mass index (BMI), were collected. Logistic regression analysis was used to recognize the risk factors of osteoporosis in patients with cirrhosis. A total of 446 patients were included in this study: 217 had liver cirrhosis (male, 74.2%; mean age, 57.2 ± 10.27) and 229 were matched controls (male, 69%, mean age, 56.69 ± 9.37). Osteoporosis was found in 44 patients (44/217, 20.3%). The spine and hip BMD in cirrhotic patients were significantly lower than that in controls. When the cirrhotic and control subjects were stratified by age, gender, and BMI, the significant difference was also observed in women patients, patients older than 60, and patients with BMI < 18. Multivariate analysis showed that the older age [odds ratio (OR) = 1.78, P  = .046], lower BMI (OR = 0.63, P  = .049), greater fibroscan score (OR = 1.15, P  = .009), and liver cirrhosis induced by alcohol liver disease (OR = 3.42, P  < .001) were independently associated with osteoporosis in cirrhotic patients. Osteoporosis occurred in about one-fifth of patients with liver cirrhosis, which was associated with age, BMI, Fibroscan score, and alcohol liver disease related liver cirrhosis. Abstract : Supplemental Digital Content is available in the text